International Monetary Fund and Private Business Transactions. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1965)
This paper analyzes legal impact of the Articles of Agreement of the IMF on the business transactions of private persons and corporations. At the heart of the Articles is the simple idea that the member states of the IMF should observe certain rules of good conduct in monetary policy, and that when it becomes difficult to observe these rules, the strain could be reduced by assistance made available from the financial resources of the IMF. This paper focuses on major obligations of good conduct that are binding on member states. It also examines legal rules of so-called public policy or ordre public, which are not explicit but can nevertheless be drawn from the Articles.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet